Endotracheal intubation with a lightwand or a laryngoscope results in similar hemodynamic variations in patients with coronary artery disease (2003)
Purpose: To asses the cardiovascular changes after either lightwand or conventional laryngoscopic endotracheal intubation (EI) in patients with coronary artery disease. Methods: Following Institutional approval and informed consent, 80 consecutive patients undergoing elective coronary artery bypass grafting were enrolled in this prospective, controlled, single-blinded study. General anesthesia was induced with fentanyl 5 ?·kg-1 and thiopental 5 mg·kg-1 followed by pancuronium 0.1 mg·kg-1. After loss-of-eyelash reflex the lungs were manually ventilated with 2% isoflurane in oxygen for five minutes. Patients were then randomly allocated to receive either the lightwand (lightwand group, n = 41) or direct-vision laryngoscopy (laryngoscopy group, n = 39). Heart rate (HR) and direct blood pressure were recorded before induction, after induction but before EI, during EI, immediately after EI and at ten-second intervals for the following five minutes. Hemodynamic management during induction was standardized. Hypotension was treated with volume replacement, ephedrine, or phenylephrine as indicated; hypertension was treated with iv nitroglycerin; tachycardia. was treated with boluses of esmolol; and, bradycardia was treated with atropine or ephedrine. Results: In both groups, mean arterial blood pressures and HR increased significantly after EI. There was a tendency for the lightwand group to have lower arterial blood pressures and slower HR. However, the differences between the two groups did not reach statistical significance. Requirements for drugs to control HR and mean arterial pressure were similar in both groups. Conclusion: In patients with coronary artery disease using a lightwand intubation technique does not modify the hemodynamic response associated with EI as compared with standard direct-vision laryngoscopy.